An optimized YOLO‐based object detection model for crop harvesting system - Junos, Mohamad Haniff; Mohd Khairuddin, Anis Salwa; Thannirmalai, Subbiah; Dahari, Mahidzal (IET image processing, 2021)
The adoption of automated crop harvesting system based on machine vision may improve productivity and optimize the operational cost. The scope of this study is to obtain visual information at the plantation which is crucial in developing an intelligent automated crop harvesting system. This paper aims to develop an automatic detection system with high accuracy performance, low computational cost and lightweight model. Considering the advantages of YOLOv3 tiny, an optimized YOLOv3 tiny network namely YOLO‐P is proposed to detect and localize three objects at palm oil plantation which include fresh fruit bunch, grabber and palm tree under various environment conditions. The proposed YOLO‐P model incorporated lightweight backbone based on densely connected neural network, multi‐scale detection architecture and optimized anchor box size. The experimental results demonstrated that the proposed YOLO‐P model achieved good mean average precision and F1 score of 98.68% and 0.97 respectively. Besides, the proposed model performed faster training process and generated lightweight model of 76 MB. The proposed model was also tested to identify fresh fruit bunch of various maturities with accuracy of 98.91%. The comprehensive experimental results show that the proposed YOLO‐P model can effectively perform robust and accurate detection at the palm oil plantation.